A Retrospective Study of Dexamethasone, Remdesivir, and Baricitinib in Severe COVID-19. (6th July 2022) - Ngo, Dallis Q.; Hamid, Kewan; Rana, Haris; Cardinale, Maria; Frenia, Douglas; Ghani, Nabil; Redel, Henry
Abstract : Purpose . RECOVERY, ACTT-1, and ACTT-2 trials have demonstrated that utilization of dexamethasone, remdesivir, or a combination of remdesivir with baricitinib leads to mortality benefit and faster time to recovery, respectively. However, no studies have investigated the benefit of triple therapy of dexamethasone, remdesivir, and baricitinib. We investigate the benefits of triple therapy compared to dual therapy of dexamethasone with remdesivir in patients with severe COVID-19 on HFNC. Materials and Methods . A retrospective data analysis was performed on patients with severe COVID-19 requiring HFNC and evaluated for hospital discharge status, requirement of mechanical ventilation, length of stay, and days on HFNC. Results . Among 191 patients with severe COVID-19, 81 patients received dexamethasone, remdesivir, and baricitinib. Patients receiving triple therapy had a significant survival benefit (HR 0.52; P = 0.042 ). Treatment with triple therapy vs. dual therapy also trended towards less requirement of mechanical ventilation (OR 0.66; P = 0.26 ). There was no significant change in length of stay (mean 13.74 vs. 13.31; P = 0.74 ) or days on HFNC (mean 8.95 vs. 7.28 days, P = 0.16 ). Conclusions . The use of dexamethasone, remdesivir, and baricitinib in patients with severe COVID-19 requiring HFNC was associated with a significant survival benefit in comparison to dual therapy of dexamethasone with remdesivir.